(untitled) (Informatica, 2019)
The authors present a solution to the problem of generating the maximum possible number of symbols for a biomolecular computer using restriction enzyme BbvI and ligase as the hardware, and transition molecules built of double-stranded DNA as the software. The presented solution offers an answer to the open question, in the algorithm form, of the maximal number of symbols for a biomolecular computer that makes use of the restriction enzyme BbvI.